Organizational Commitment of People Working For Turkish Sports Management Organizations In Terms of Some Variables - Murat Kalfa; Merve Karaman; Dilek Tufan (European Scientific Journal, ESJ, 2016)
The aim of this study is to identify and examine the organizational commitment levels of the people working for General Directorate of Sports and Sports Federations that form the main structure of Turkey national sports management organization regarding some variables. Sampling of the study consisted of 105 female and 142 male, totally 247 participants whose age averages were 40.53± 9.86 working for General Directorate of Sports and Sports Federations that form the main structure of Turkish national sports management organization. Organizational Commitment Questionnaire (OCQ) was used to identify organizational commitment levels of the employers. Since the data did not meet the parametric hypotheses, nonparametric Kruskall-Wallis and Man-Whitney U tests were used to analyze organizational commitment levels in terms of variables. Results of the analysis revealed that organizational commitment and its sub dimensions emotional, normative and attendance commitment levels were at moderate level. Considering education levels, getting in-service training and quality inservice training conditions, there was not any significant difference at organizational commitment level and sub dimensions; however, there were significant differences in terms of the ages, marital statuses, the institution they worked for, their position, and whether they chose their job voluntarily or not. In conclusion, the ones who were above 40, married, working for federation, chose their jobs voluntarily, were senior executives, and section leaders had higher organizational commitment levels.